Formaldehyde incorporation by a new methylotroph (L3). - Hirt, W (1978)
A number of bacterial strains have been isolated and investigated in our search for a promising organism in the production of single-cell protein from methanol. Strain L3 among these isolates was identified as an obligate methylotroph which grew only on methanol and formaldehyde as the sole sources of carbon and energy. The organism also grew well in batch and chemostat mixed-substrate cultures containing methanol, formaldehyde, and formate. Although formate was not utilized as a sole carbon and energy source, it was readily taken up and oxidized by either formaldehyde- or methanol-grown cells. The organism incorporated carbon by means of the ribulose monophosphate pathway when growing on either methanol, formaldehyde, or various mixtures of C1 compounds. Its C1-oxidation enzymes included phenazine methosulfate-linked methanol and formaldehyde dehydrogenase and a nicotinamide adenine dinucleotide-linked formate dehydrogenase. Identical inhibition by formaldehyde of the first two dehydrogenases suggested that they are actually the same enzyme. The organism had a rapid growth rate, a high cell yield in the chemostat, a high protein content, and a favorable amino acid distribution for use as a source of single-cell protein. Of special interest was the ability of the organism to utilize formaldehyde via the ribulose monophosphate cycle.